Towards the standardization of Hydra vulgaris bioassay for toxicity assessments of liquid samples - G. Farley; P. Bouchard; C. Faille; S. Trottier; F. Gagné (Ecotoxicology and Environmental Safety)
The Hydra vulgaris bioassay is recognized as sensitive invertebrate test species for toxicity assessment of real-life environmental mixtures for enforcement and monitoring investigations. The purpose of this study was to characterize the intra-laboratory variability, study the influence of environmental variables (temperature, luminosity, inter-individual and day of analysis) on ZnSO4 toxicity, a reference model toxicant for hydra. The sublethal (effect concentration for 50 % of hydra-EC50) and lethal (lethal concentration for 50 % of hydra-LC50) were determined based on characteristic morphological changes for this species. The influence of water hardness, ammonia and dissolved oxygen for over 50 real-life environmental liquid mixtures (effluents and leachates) were examined and compared with rainbow trout and Daphnia magna acute lethality tests. A control chart for Zn was developed from over 40 trials yielding an 96 h LC50 of 0.7 mg/L (0.66–0.77 95 % confidence interval-CI) and EC50 of 0.19 mg/L (0.17–0.21 95 % CI). The influence of 8 different analysts, the trial days and luminosity did not significantly influence the LC50 and EC50. Only higher temperature significantly decreased the toxicity of ZnSO4 within 15–30 °C range. The hydra bioassay was then practiced on more than 50 real-life effluents/leachates and compared with the 96 h rainbow trout and 48 h Daphnia magna survival tests. The data revealed that water hardness, dissolved oxygen and ammonia were not significantly correlated with either the LC50 or EC50 values. Moreover, the hydra LC50 data predictive (rank correlation of 0.6) the rainbow trout LC50 with the absence of false negatives. The hydra data were at least as if not more sensitive than the rainbow trout LC50 making it a relevant alternative method to reduce fish use for screening potentially toxic environmental mixtures.